Teacher Candidates' Involvement with Reading Interventions in High Needs Schools: Wrestling with the Everyday - Steve Sider; Christina Belcher (University of Windsor, 2015)
The demands on new teachers as they enter the teaching profession are extensive and deep-rooted. This article provides insight into how faculty within a teacher education program in Ontario, Canada considered one service program emphasis and how it shed light into the everyday world of teacher candidates as they wrestled with the everyday activity of trying to support struggling readers. We identify this process of forging relationships and developing professional skills as we examine the experiences and reflections of teacher candidates as they journey through their involvement with the program. As such, we take Dorothy Smith's (2005) perspective that the everyday world is problematic. Those things which we take for granted, and assume to be obvious, or have been assumed by reading research to be normative, are not necessarily so.